Hubungan Social Support Dengan Tingkat Kesepian Lanjut Usia Pada Latar Belakang Pedesaan Di Kabupaten Bogor - Herma Rahayu, Vira; Asmawati, Wa Ode (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
The solidarity life of mechanical communities in rural areas generally has closer social ties than organic communities in urban areas. It seems to be a gap between what is expected and reality if rural mechanical solidarity is still able to make the elderly feel lonely in the midst of deep-rooted social ties. This study aims to determine the relationship between social support and the level of loneliness of the elderly using THE MPSS scale and UCLA Loneliness Scale Version 3. This quantitative study involved 91 elderly participants in Barengkok Village, Bogor Regency. Parametric analysis to see the relationship between independent and dependent variables using Pearson Product Moment. The results showed a negative correlation (r = -0.629 and p = 0.000) which indicates that if social support increases, the level of loneliness decreases. The implication of this study is that the elderly need to be given social support either from a partner, family or friends so that the elderly do not feel lonely.